PENGARUH KEPEMILIKAN MANAGERIAL, KEBIJAKAN HUTANG, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia) (Students' Journal of Accounting and Banking, 2014)
The purpose of the company in general is for profit. company also expects continuous growth to maintain the viability of the company, who will also have to provide greater welfare to its shareholders. Therefore, companies need to implement a dividend policy that benefits both the company and the shareholders. The purpose of this study was to determine the effect of managerial ownership, debt policy, profitability, and firm size on dividend policy (Case Study In Banking Companies Listed in Indonesia Stock Exchange). The population in this study are all banking companies listed Exchange Indonesia Stock Exchange (IDX). Sample selection techniques using Purpose Sampling methods. The analytical tool used is multiple linear regression. The results showed that managerial Ownership significant negative effect on the House of Representatives. Policy Debt significant positive effect on the House of Representatives.Significant positive effect on the profitability of the House. Negative effect of firm size is not significant to the House. Keywords: managerial ownership, debt policy, profitability, firm size and dividend policy